Praktik Kerjasama Bagi Hasil Penggarap dengan Pemilik Lahan Sawah terhadap Kesesuaian Konsep Akad Mukhabarah: Studi Kasus di Desa Talang Jarang Kabupaten Bengkulu Utara - Tini Angreyina; Khairiah Elwardah; Uswatun Hasanah (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this study was to determine how the practice of profit-sharing cooperation between cultivators and rice field owners is in accordance with the concept of the mukhabarah agreement in Talang Jarang Village, North Bengkulu Regency. This study used a qualitative method. The informants in this study were 15 people, using primary data and supplementary data using secondary data in the form of data from books, documents, and journals. Data collection techniques were observation, interviews, and documentation. The results of this study can be concluded that the practice of profit-sharing cooperation between cultivators and rice field owners in Talang Jarang Village, North Bengkulu Regency, is still carried out traditionally with a hereditary system. The agreement used is an oral agreement based on trust without a written contract. The distribution of the harvest is generally carried out with a 50:50 or 60:40 scheme, but in some cases, there is a unilateral change in the agreement by the landowner during the harvest, which is detrimental to the cultivator. This system is largely in accordance with the concept of the mukhabarah agreement in Islam, where the cultivator bears all the costs of land management. However, the main challenges faced are the lack of clarity in the term of the agreement, changes to the agreement that are detrimental to the cultivators, and the absence of a written contract that can trigger conflict. Therefore, a more transparent agreement system and clear mechanisms are needed to ensure fairness for both parties.